Efficacy and safety of coadministration of sitagliptin with insulin glargine in type 2 diabetes: 西格列汀联合甘精胰岛素治疗2型糖尿病的疗效及安全性. (22nd September 2016) - Cao, Ying; Gao, Fang; Zhang, Qian; Xu, Lingling; Wan, Qian; Li, Wenqi; Li, Jimin; Wang, Ling; Xue, Yaoming
Abstract: Background: The aim of the randomized present study was to compare the therapeutic efficacy and safety of a combination of sitagliptin, a dipeptidyl peptidase (DPP)‐4 inhibitor, plus insulin glargine (GL + sita) with that of premixed insulin aspart 30 (NOV) for type 2 diabetes (T2D) patients controlled with oral hypoglycemic drugs (HbA1c 7 %–9 %). Methods: Sixty‐five patients were randomized (1: 1) to the GL + sita (n = 33) and NOV (n = 32) groups and were treated with the combination regimen or premixed insulin twice a day for 16 weeks. The primary endpoint was mean change in HbA1c. Secondary endpoints included fasting blood glucose, blood glucose profiles (seven time points), rate of achieving target HbA1c (<7 % or ≤6.5 %), insulin dose, incidence of hypoglycemia, and body weight. Results: After 16 weeks, there was no significant difference in HbA1c between the two groups, although more patients achieved HbA1c <7.0 % in the GL + sita group. There was a significant difference in body weight changes between the GL + sita and NOV groups (−0.45 vs 1.52 kg, respectively; P < 0.001). Mean plasma glucose and the mean amplitude of glycemic excursion were significantly lower in the GL + sita than NOV group ( P < 0.005), as was the incidence of symptomatic hypoglycemia (2.85 % vs. 13.3 %, respectively; P < 0.001). Conclusion: The combination of GL + sita greatly improved HbA1c in T2D patients (HbA1c 7 %–9 %) with an efficacy that was equal to that of premixed insulin. Thus, GL + sita treatment is a viable option for patients who fail to achieve glycemic control using oral hypoglycemic drugs. Highlights: Our study demonstrates that insulin glargine combined with sitagliptin phosphate (100 mg/day) is an effective and safe choice for the treatment of type 2 diabetes patients who fail to respond to oral hypoglycemic drugs with HbA1c levels of 7%–9%. Its efficacy in terms of blood glucose control was equivalent to that achieved by treatment with premixed insulin alone, and achieved stable glucose control with obvious advantages in terms of the incidence of hypoglycemia, weight gain and health economics. Percentage of patients reaching HbA1c targets of (a) ≤6.5 % and (b) ≤7.0 % in the sitagliptin plus insulin glargine (GL + sita) and premixed insulin aspart 30 (NOV) groups after 16 weeks treatment. [Correction added on 27 January 2017, after first online publication: the label of Figure 3(b) has been corrected from 'Patients with HbA1c ≤ 7.2%' to '% Patients with HbA1c ≤ 7.0%'.]